MANAGEMENT OF LEGAL PRODUCT DOCUMENTS AT THE LEGAL AND HUMAN RIGHTS BUREAU OF THE RIAU ISLANDS REGIONAL SECRETARIAT - Arman, Zuhdi; Siagian, Anna Andriany; Sari, Sari (eScience Humanity Journal, 2023)
This study aims to determine the activities of document management of legal products in legal counseling activities at the Bureau of Law and Human Rights at the Regional Secretariat of the Riau Islands Province. The method used is qualitative research with a study approach. Data collection techniques were carried out through observation and literature study. Data analysis techniques were carried out using data analysis techniques according to Miles and Huberman, namely Data Reduction, Data Display and Conclusion Drawing. The results showed that the activities of managing legal product documents at the Bureau of Law and Human Rights of the Regional Secretariat of the Riau Islands Province followed the rules of documentation which included recording which included activities of formulation, organization which included preparation and storage activities as well as socialization which included extension and socialization activities. Based on the results of the study, it can be concluded that the management of legal product documents at the Bureau of Law and Human Rights of the Regional Secretariat of the Riau Islands Province has been carried out in accordance with the rules of documentation.